From Zoning Based Area To A Hybrid Space; The Transformation Strategies - FARHAN ABDULLAH ALI (Journal of Contemporary Urban Affairs, 2019)
One of the contemporary city`s ambition nowadays is to be more comfortable, flexible and coeval. Although numerous urban design attempts have appeared to enhance the user’s gratification, there are urgent demands to upgrade the classical public space to be more agreeable with the necessities of everyday life. Most of the urban areas after industry era are zoning based, meanwhile, have been less adaptable to daily life conditions economically, environmentally and psychologically alike. The zoning based space has a single- activity such as public or private, workspace or leisure space, etc., while the urgent demand is to look for kind of space, has mixed -activities that give it more richness, diversity, and interaction. This type of Heterotopic space has potentials, characteristics, and efforts that reconcile everyday life requirements. On another hand, it could be defined, as a smart space, which is more correspondent with technological development through applying the digital technologies involved it. This paper is an attempt to reframe the principles of creating public space and portrays the features of transforming the zoning based area into a hybrid one. In addition, it aims to implement deconstructive approach tools as strategies for enhancing user satisfaction in public space. The paper adopts a comparative approach that criticizes the zoning theory from different perspectives according to numerous situations and it accepts the hybrid space theory as a substitutional possibility to deconstruct the typical public space.